Substance P Increases the Excitability of Dorsal Motor Nucleus of the Vagus Nerve via Inhibition of Potassium Channels - Yang, Eunhee; Kim, Woojin; Park, Yong Seek; Jin, Young-Ho (Frontiers in Neuroscience, 2022)
Increases in the substance P (SP) concentration in the medial portion of the dorsal motor nucleus of the vagus nerve (mDMV) in the brainstem are closely associated with chemotherapy induced nausea and vomiting (CINV). However, the underlying cellular and molecular mechanisms of action are not well understood. In this study, we investigated the effects of SP on mDMV neurons using whole-cell patch-clamp recordings from rat brainstem slices. Application of different concentrations of SP induced tonic and phasic responses. Submicromolar concentrations of induced an inward shift of the holding current by increasing membrane input resistance. The response was mimicked by acidification of the extracellular solution and inhibited by a neurokinin type 1 receptor antagonist. These responses have equilibrium potentials close to the K+ equilibrium potential. In addition, a TWIK-related acid-sensitive K+ channel 3 (TASK-3) inhibitor, PK-THPP, induced responses similar to those produced by submicromolar SP concentrations. Micromolar concentrations of SP facilitated γ-aminobutyric acid (GABA) release but diminished glutamate release; these changes were blocked by a GABAB receptor antagonist and a neurokinin type 3 receptor antagonist, respectively. In current-clamp recordings, submicromolar SP concentrations increased neuronal excitability by depolarizing membrane potentials. However, neither the increase in SP concentration to the micromolar range nor the addition of GABAA and ionotropic glutamate receptor antagonists affected neuronal excitability. Thus, SP increases the excitability of mDMV neurons by inhibiting K+ conductance.